GROWING ROLE OF TEACHERS IN INDEPENDENCE CHILDREN AGE 2-4 YEARS - Yaswinda, Mrs. (Indonesian Journal of Early Childhood Education Studies, 2013)
Children need adults to help assess the limits of shame and doubt so that they become independent. If the definition of independence for adolescents and adults is the ability to take responsibility for what is done without burdening others, while for early childhood are the capabilities that are tailored to the task of development. The role of early childhood teachers, among others;(1)Planners, It is very important early childhood teacher to make curriculum plan must take steps independence of children aged 2-4 years. (2) Facilitators, As a facilitator, the teacher becomes the implementing learning by carrying out planned activities (3) Models Ininstill self-reliance in children, early childhood teachers must be able to serve as a model for children. Teacher who exemplifies the independence of the together with other children (4) Observers. Observation is carried out data collection tool to record / records in a systematic behavioral symptoms that appear.